1998
DOI: 10.1007/s001620050091
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation Structure and Spectra in Turbulent Channel Flow

Abstract: Abstract. The strong mean shear in the vicinity of the boundaries in turbulent boundary layer flows preferentially amplifies a particular class of perturbations resulting in the appearance of coherent structures and in characteristic associated spatial and temporal velocity spectra. This enhanced response to certain perturbations can be traced to the nonnormality of the linearized dynamical operator through which transient growth arising in dynamical systems with asymptotically stable operators is expressed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…All of these studies demonstrate encouraging agreement between predictions resulting from stochastically driven linearized models and available data and highlight the challenges that arise in modeling dissipation and the statistics of forcing (DelSole 2000(DelSole , 2004. Farrell & Ioannou (1998) examined the statistics of the NS equations linearized around the Reynolds-Tiederman velocity profile subject to white stochastic forcing. It was demonstrated that velocity correlations over a finite interval determined by the eddy turnover time qualitatively agree with second-order statistics of turbulent channel flow.…”
Section: Stochastic Forcing and Flow Statisticsmentioning
confidence: 81%
See 1 more Smart Citation
“…All of these studies demonstrate encouraging agreement between predictions resulting from stochastically driven linearized models and available data and highlight the challenges that arise in modeling dissipation and the statistics of forcing (DelSole 2000(DelSole , 2004. Farrell & Ioannou (1998) examined the statistics of the NS equations linearized around the Reynolds-Tiederman velocity profile subject to white stochastic forcing. It was demonstrated that velocity correlations over a finite interval determined by the eddy turnover time qualitatively agree with second-order statistics of turbulent channel flow.…”
Section: Stochastic Forcing and Flow Statisticsmentioning
confidence: 81%
“…Furthermore, Chernyshenko & Baig (2005) used the linearized NS equations to predict the spacing of near-wall streaks and relate their formation to a combination of lift-up due to the mean profile, mean shear, and viscous dissipation. The linearized NS equations also reveal large transient growth of fluctuations around turbulent mean velocity (Butler & Farrell 1993;Farrell & Ioannou 1993a) and a high amplification of stochastic disturbances (Farrell & Ioannou 1998). Schoppa & Hussain (2002) ;Hoepffner, Brandt & Henningson (2005a) further identified a secondary growth (of the streaks) which may produce much larger transient responses than a secondary instability.…”
Section: Linear Analysis Of Transitional and Turbulent Shear Flowsmentioning
confidence: 86%
“…Attempts have been made to use linear analysis to explain the dominant features of turbulent flow in terms of optimal transient modes 5, 10 or stochastic forcing. 11,12 The present analysis is closer to a resolvent or system norm analysis. 13,14 A different approach by other authors [15][16][17] has developed exact solutions of the Navier-Stokes equations, giving rise to unstable coherent structures, as the foundations of transitional flow and/or near-wall turbulence.…”
Section: A Non-normality and Algebraic Disturbance Growthmentioning
confidence: 87%
“…Relevance of the stochastic forcing analysis When trying to relate the results of the present analysis to experimental observations of unforced turbulent flows, considering stochastic forcing is probably more relevant than considering harmonic forcing. In the spirit of Farrell & Ioannou (1994) and Farrell & Ioannou (1998), the stochastic forcing can be assumed to be a surrogate for the nonlinear terms that are neglected in the linearized model. The distribution V (α, β) would then represent the linear amplification of the variance of the nonlinear terms, where the whole variance integrated in the wall-normal direction is considered.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pre-multiplied energy amplifications allows us then to analyse the deviations from the β-power-law behaviour and to identify the spanwise scales associated to the most amplified structures in the near wall and at large scales. Previous similar investigations have not detected the approximate β-power scaling of the amplifications of log-layer structures, either because the molecular viscosity instead of the turbulent eddy viscosity was used in the linearized equations (Farrell & Ioannou 1998) or because a too low Reynolds number was considered ). This paper is organized as follows: in § 2, we briefly introduce the considered turbulent mean base flow, the associated eddy viscosity and the equations satisfied by small coherent perturbations to the base flow.…”
Section: Introductionmentioning
confidence: 99%